Hubungan Soft Skills dan Prestasi Praktik Industri dengan Kesiapan Siswa Memasuki Dunia Kerja - Thomas Aditya Santoso; Dwi Agus Sudjimat; Suwarno Suwarno (Fakultas Teknik Universitas Negeri Malang, 2019)
This research aimed to find the relation between soft skills and industrial practices achievement with students' readiness to enter the working world. The population of this research were the Class XII students of Mechanical Engineering Skill Competency from Canda Bhirawa Vocational High School Kediri Regency. The samples were determined using random sampling based on the Slovin formula. The soft skills and students' work readiness variables data were collected using a questionnaire, whereas the industrial practices achievement variable was obtained from the score documents provided by the school. The data that were collected were analyzed using regression technique. The results showed that there was a strong, positive, and significant correlation between soft skills and students' readiness in entering the working world, there was a medium, positive, and significant correlation between industrial practice achievements with students' readiness to enter the working world. And there was a solid, positive, and significant cooperation correlation between soft skills and industrial practices achievement with students' readiness to enter the working world.